Evaluation of nutritional values of tree-forage legume leaves from Gunungkidul District, Indonesia - I NYOMAN GUNA DARMA; ANURAGA JAYANEGARA; AHMAD SOFYAN; ERIKA BUDIARTILACONI; MUHAMMAD RIDLA; HENDRA HERDIAN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Darma ING, Jayanegara A, Sofyan A, Budiartilaconi E, Ridla M, Herdian H. 2023. Evaluation of nutritional values of tree-forage legume leaves from Gunungkidul District, Indonesia. Biodiversitas 24: 2733-2744. This study aimed to assess the nutritional value of tree legume leaves found in Gunungkidul District. A completely randomized design with 19 treatments (legume species) and six replications (nylon bags) was employed. The study evaluated the chemical composition, in sacco dry and organic matter degradation characteristics, and their correlation with the chemical composition. The results indicated variations in the crude protein (CP) content (12.44% to 26.9%), crude fiber (CF) content (16.13% to 27.38%), total digestible nutrients (TDN) (71.10% to 88.17%), and total phenol content (2.47% to 21.87%) on a dry matter basis. Among the legume species, Indigofera tinctoria L. exhibited the highest soluble fraction (a) values for dry matter (42.89±1.15%) and organic matter (40.32±1.37%). Additionally, I. tinctoria displayed the highest potential degraded fraction values (a+b) for dry matter (88.33±0.90%) and organic matter (88.12±0.95%). The effective degradation of dry matter (EDDM) and organic matter (EDOM) were 64.57±0.48% and 63.78±0.68%, respectively. The correlation coefficients (r) between ash, CP, TDN, CF, total phenol, and EDDM and EDOM values were 0.54, 0.58, 0.53, -0.73, -0.53, and 0.52, 0.55, 0.52, -0.72, -0.56 respectively. In conclusion, tree-forage legume leaves from Gunungkidul District exhibited varying nutritional values, with I. tinctoria showing the highest values for effective dry and organic matter degradation compared to other tree legumes. The ash content, CP, and TDN demonstrated positive correlations with the EDDM and EDOM values, whereas the CF content and total phenol exhibited negative correlations with the EDDM and EDOM values of tree legume leaves.